Analysis of plane wave propagation under the purview of three phase lag theory of thermoelasticity with non-local effect - Tiwari R.; Kumar R. (My University, 2025)
Present study characterizes the propagation of harmonic plane waves in Eringen's non-local thermoelastic medium. Three phase lag (TPL) theory of thermoelasticity has been applied to account for the interactions between elastic and thermal fields. Two sets of coupled longitudinal waves (elastic and thermal) and one independent vertically shear wave have been achieved. Longitudinal waves are found to be dispersive and experience attenuation. All these waves are found to be influenced by the elastic non-local parameter. Further shear-type wave obtains a critical frequency while the coupled longitudinal waves may face critical frequencies conditionally. High and low frequency asymptotes of physical fields have been calculated. By considering an illustrative example, numerical results have been computed to explore the physics of the problem. The results for the TPL model have been compared with those for the dual phase lag theory. The study reveals that the distribution of phase velocities and attenuation coefficients for the TPL model are significantly different from those of the dual phase lag models with respect to the frequency as well as non-local elastic parameter. TPL theory is found to be capable in predicting better results as compare to the dual phase lag theory of thermoelasticity. © 2021 Elsevier Masson SAS